2019
DOI: 10.1101/533588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The vagino-cervical microbiome as a woman’s life history

Abstract: The vagina contains at least a billion microbial cells, which are dominated byLactobacilli. Here we perform metagenomic shotgun sequencing on cervical samples from 1148 women. Factors such as pregnancy, delivery histories and breast-feeding were all more important than menstrual cycle in shaping the microbiome. Bifidobacterium breve was seen with older age at sexual debut;Lactobacillus crispatus negatively correlated with pregnancy history; potential markers for lack of menstrual regularity, heavy flow, dysmen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…Due to the emphasis on diet in early studies and recently on medication, MWAS 1,31 have received even more controversy than GWAS. Besides diet and medication, we also took into account physical activity in this 4D-SZ cohort 44,45 . Here we find that fecal biomarkers previously reported by MWAS studies on colorectal cancer and metabolic diseases have some associations with host genetics, whereas some taxa especially some spore-forming bacteria lacked host genetic associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the emphasis on diet in early studies and recently on medication, MWAS 1,31 have received even more controversy than GWAS. Besides diet and medication, we also took into account physical activity in this 4D-SZ cohort 44,45 . Here we find that fecal biomarkers previously reported by MWAS studies on colorectal cancer and metabolic diseases have some associations with host genetics, whereas some taxa especially some spore-forming bacteria lacked host genetic associations.…”
Section: Discussionmentioning
confidence: 99%
“…632 individuals were enlisted in the discovery cohort and 663 individuals were enlisted in the replication cohort, as part of the larger effort of 4D-SZ study 44,45 . Questionnaires were collected through a cell phone application.…”
Section: Cohort Descriptionsmentioning
confidence: 99%
“…In order to substantially increase the amount of oral microbiome data, we shotgun sequenced 2284 saliva and 391 tongue dorsum samples from the 4D-SZ cohort 3, 12, 22 , 671 saliva samples from five ethnic groups of Yunnan province, producing over 43.19 terabytes of sequence data ( Supplementary Table 1 ). Together with 808 published samples from 5 studies 6, 2326 that have not been used for metagenomic assembly ( Supplementary Table 1 ), a total of 4,154 oral samples with metagenomic data were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…A number of taxa with compact genomes were identified in this study, such as CPR and Mollicutes. Mollicutes such as Mycoplasma and Ureaplasma are well known in the female reproductive tract 22 . Much remains to be elucidated for the metabolic requirement of small bacteria in the oral microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…to maintain a balanced pH for themselves. The top one for gut microbes may be glutamate decarboxylase (produces GABA (γ-aminobutyric acid) from glutamate), while histidine decarboxylase in the female reproductive tract might contribute to menstrual pains 75 . Besides, recent studies identified tyrosine decarboxylases in gut microbes that could digest the medication levodopa used to treat Parkinson’s disease 76, 77 .…”
Section: Discussionmentioning
confidence: 99%